Pyroptosis: A new insight of non-small-cell lung cancer treatment - Chen, Xi; Wu, Jianzhang; Wang, Jiabing (Frontiers in Oncology, 2022)
Non-small cell lung cancer (NSCLC) has become one of the most common malignant tumors. Emerging evidence has shown that tumor resistance to apoptosis by damaging or bypassing apoptotic cell death is a major contributor to poor responses to therapy in patients with NSCLC. Pyroptosis is a new type of cytolytic and inflammatory programmed death distinct from apoptosis. Currently, pyroptosis has been reported to cause a strong inflammatory response and significant tumor suppression. It is considered a promising therapeutic strategy and prognosis for NSCLC. In this review, we summarized the characteristics of pyroptosis from its underlying basis and role in NSCLC, thereby providing the potential of pyroptosis as a therapeutic strategy and highlighting the challenges of activating pyroptosis in NSCLC treatment.